Surface treatment-controlled solvothermal synthesis of highly active reduced 1D titania with heterojunctioned carbon allotrope - Ahmed Badreldin (9574341) (2022)
One-dimensional (1D) nanowire black titania heterojunctioned with multi-wall carbon nanotube (bTiO2 NW/MWCNT) structures were successfully synthesized via a facile single-step hydrothermal procedure, coupled with succeeding surface treatments and a solid-state physiochemical mode of reduction. Paramagnetic SiO2-coated Fe3O4 microspheres were fabricated and used as cores for the seeding and growth of the bTiO2 NW/MWCNT photocatalyst. The as-prepared photocatalysts were characterized via X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoemission spectroscopy, Fourier transform infrared spectroscopy, and UV-vis diffuse reflectance spectroscopy. The results of materials characterization confirmed formation of 1D bTiO2 NW structure with chemically bound MWCNT atop the reduced Ti3+ propagated lattice of the predominantly (101) exposed facets of anatase TiO2. Controlling the surface treatment process and NW growth time to maintain the anatase phase and stability of surface morphology upon reduction allowed for superior visible light-driven photoactivity. The visible light-driven photocatalytic degradation of 10 mg/L methylene orange was recorded at 97.4% in 20 min of 0.7 Sun intensity. The apparent reaction rate constant (k) of the as-prepared photocatalyst (0.1439 min−1) is ~ 18 times higher than that of pristine TiO2. Utilization of paramagnetic cores for in situ photocatalyst collection upon water treatment is highly recommended for newly developed materials. Further, performing surface treatment procedures of prepared titania-based photocatalysts has been proven to have a notable advantageous effect on photoactivity and is thus suggested for similar materials. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42247-021-00162-0